The fractured history of the mental hospital in Delhi - Jain, Sanjeev (Indian J Psychiatry, 2018)
The history of the mental hospital in Delhi is a fascinating story. Set up in colonial times, the asylum in Delhi seems to reflect the tumultuous and chaotic history of the city itself. It was perhaps established in the early 19(th) century, and functions till 1857, when it is ransacked in the Mutiny. It is subsequently merged with the asylum at Lahore in 1861, set up again, and incredibly, closed again at the turn of the century. Subject to the whims of administrators and policy makers, the asylum then ceases to exist till the 1960s when a new avatar appears. In it's non continuity is the story of the neglect of mental illness.